Amniotic epithelial cells accelerate diabetic wound healing by protecting keratinocytes and fibroblasts from high‐glucose‐induced senescence. (3rd February 2022) - Shu, Futing; Gao, Haojie; Wu, Wenfeng; Yu, Shaoshuo; Zhang, Lianjie; Liu, Huazhen; Xiao, Shichu; Xia, Zhaofan; Zheng, Yongjun
Abstract: Human amniotic epithelial cells (hAECs), one of the stem cells identified from the human placenta, possess numerous advantages and have been considered as an attractive and available cell source for regenerative medicine. Accumulating evidence has showed that cellular senescence was one of the pathogenic hubs of diabetic wound chronicity. Keratinocytes and fibroblasts are the primary cells involved in wound healing. Therefore, in this study, we aimed to investigate the anti‐senescence effects of hAECs on keratinocytes and fibroblasts in diabetic wounds. Sustained hyperglycemia impaired cell function and accelerated senescence in vitro. However, this phenotype was rescued by hAECs‐conditioned medium (hAECs‐CM), with increased migration and proliferation in keratinocytes and fibroblasts and enhanced collagen synthesis and α‐smooth muscle actin (α‐SMA) production in fibroblasts. In addition, hAECs‐CM dramatically inhibited intracellular reactive oxygen species (ROS) and senescence‐associated β‐galactosidase (SA‐β‐gal) in keratinocytes and fibroblasts under high‐glucose (HG) condition. Moreover, hAECs‐CM could downregulate the increased RAGE and P21 induced by continuous HG stimulation. Intradermal injection of hAECs in diabetic wounds promoted re‐epithelialization and granulation tissue formation, accompanied by decreased P21 + cells and increased PCNA + cells in epidermis and dermis, as well as promoted collagen deposition and α‐SMA expression. Furthermore, CM‐Dil‐labeled hAECs survived to Day 5 but disappeared by Day 10 in diabetic wounds. These findings indicated that hAECs could inhibit diabetes‐induced premature senescence and enhance the function of keratinocytes and fibroblasts via paracrine effects, partly by inhibiting RAGE/P21 signaling pathway. Thus, hAECs targeting cellular senescence induced by a hyperglycemic environment may be a new strategy for the treatment of diabetic wounds.